Inside Front Cover: Thermo‐responsive topological metamorphosis in covalent‐and‐supramolecular polymer architectures. Issue 6 (26th December 2022) - Wang, Yongming; Zhang, Hao; Zhang, Zhaoming; Zhao, Jun; Bai, Ruixue; Liu, Yuhang; Zhang, Xinhai; Yan, Xuzhou
Abstract : Abundant topological architectures are the basis of polymeric diversification. In this article (e206 ), Yan and co‐workers couple the covalent polymer and supramolecular polymer in a single system to realize an intrinsical macromolecular metamorphosis from grafted polymer to crosslinked network. The transformation elicited a shift from stiff but brittle material to a strong yet tough one.